Exercise Intervention Influences on Sleep and Anxiety in Children with Autism Spectrum Disorder: A Meta-Analyses of Randomized Controlled Trials - Wang, Jiaju; Li, Jiangyan; Wang, Feifei; You, Yang (Neuropediatrics, 2025)
Related issues, such as sleep disturbance, are also frequently reported by children with autism spectrum disorder (ASD). This study systematically reviewed the influences of exercise on sleep and anxiety in children with ASD. Search for eligible studies through four databases, and then proceed with screening. The inclusion criteria are as follows: 1) children with ASD; 2) age 3 to 14 years; 3) randomized controlled trial (RCT); 4) the intervention group received exercise training; 5) conducted pre-and posttest, which includes sleep and anxiety. Use the Cochrane bias risk assessment tool to evaluate the quality of the selected study. Select standardized mean difference (SMD) as the appropriate effect scale index, and use Revman 5.4 software to analyze the mean difference of the selected article data. A total of seven studies fulfilled the inclusion criteria and were selected for the meta-analysis. The included studies involved 387 males and 79 females. The results demonstrated that the EXP group benefited from improved sleep (SMD, −1.05 [−1.25, −0.85], p < 0.05, I2 = 27%, p for heterogeneity = 0.22) and anxiety (SMD, −1.14 [−1.56, −0.72], p < 0.05, I2 = 95%, p for heterogeneity < 0.01) than the CON group. According to the findings, physical activities could offer nonpharmacological interventions for improving sleep and anxiety in children diagnosed with ASD. Sports training could also be considered to promote the rehabilitation of children patients with ASD, which might provide valuable insights.
Keywords: randomized controlled trial; autism spectrum disorder; children with ASD